Success Stories: Inspiring People on the Autism Spectrum and Cerebral Palsy (Comparative & International Education Series, 2023)
"Success Stories: Inspiring People on the Autism Spectrum and Cerebral Palsy" is a collection of inspiring stories of individuals who have overcome challenges associated with autism spectrum disorder (ASD) and cerebral palsy (CP). This book features ten compelling stories of people who have achieved success in their personal and professional lives despite their conditions. It includes some famous people who are believed to have autism or cerebral palsy and how their conditions have shaped their lives and careers. These stories are diverse and showcase the wide range of challenges and strengths of individuals with these conditions. They highlight the importance of support, self-awareness, and resilience in overcoming challenges and achieving personal and professional success. They demonstrate that despite their challenges, individuals with these conditions can live fulfilling lives and achieve their goals.Cover Design: Sahar AghasafariCover Design: Sahar Aghasafari